Cannabinoid Signaling in Auditory Function and Development - Ghosh, Sumana; Stansak, Kendra; Walters, Bradley J. (Frontiers in Molecular Neuroscience, 2021)
Plants of the genus Cannabis have been used by humans for millennia for a variety of purposes. Perhaps most notable is the use of certain Cannabis strains for their psychoactive effects. More recently, several biologically active molecules within the plants of these Cannabis strains, called phytocannabinoids or simply cannabinoids, have been identified. Furthermore, within human cells, endogenous cannabinoids, or endocannabinoids, as well as the receptors and secondary messengers that give rise to their neuromodulatory effects, have also been characterized. This endocannabinoid system is composed of two primary ligands- anandamide and 2-arachidonyl glycerol; two primary receptors - cannabinoid receptors 1 and 2; and several enzymes involved in biosynthesis and degradation of endocannabinoid ligands including diacylglycerol lipase and monoacylglycerol lipase. Here we briefly summarize cannabinoid signaling, and review what has been discerned to date with regard to cannabinoid signaling in the auditory system and its roles in normal physiological function as well as pathological conditions. While much has been uncovered regarding cannabinoid signaling in the central nervous system, less attention has been paid to the auditory system specifically. Still, evidence is emerging to suggest that cannabinoid signaling is critical for the development, maturation, function, and survival of cochlear hair cells and spiral ganglion neurons (SGNs). Furthermore, cannabinoid signaling can have profound effects on synaptic connectivity in CNS structures related to auditory processing. While clinical cases demonstrate that endogenous and exogenous cannabinoids impact auditory function, this review highlights several areas, such as SGN development, where more research is warranted.